2002
DOI: 10.28945/2464
|View full text |Cite
|
Sign up to set email alerts
|

Language Trends in Introductory Programming Courses

Abstract: Deciding what to teach novice programmers about programming and, in particular, which programming language to teach to novice programmers, and how to teach it, is a common topic for debate within universities. Should an industry relevant programming language be taught, or should a language designed for teaching novices be used? In order to design tools and methodologies for the teaching of novice programmers it is important to uncover what is being taught, and in turn, what will be taught in the future. A cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Paul Tymann's data comes from an online survey of the SIGCSE community carried out in 2005 [96]. deRaadt et al [27,28] conducted similar surveys in Australia and New Zealand in 2001 and 2003, and a much earlier one was done by Stephenson and West in 1998 [92]. These surveys indicate that the most widely used languages have not changed during this time span -Java, C++ and C have continuously been among the top four languages.…”
Section: Language Choicementioning
confidence: 99%
See 1 more Smart Citation
“…Paul Tymann's data comes from an online survey of the SIGCSE community carried out in 2005 [96]. deRaadt et al [27,28] conducted similar surveys in Australia and New Zealand in 2001 and 2003, and a much earlier one was done by Stephenson and West in 1998 [92]. These surveys indicate that the most widely used languages have not changed during this time span -Java, C++ and C have continuously been among the top four languages.…”
Section: Language Choicementioning
confidence: 99%
“…Studies have found that market appeal/industry demand/student demand is one of the most important factors affecting language choice in computer science education [31,27,28]. As an example, Rochester Institute of Technology dropped Eiffel as its introductory programming language primarily because of student demand to learn a language that would be useful after graduation.…”
Section: Language Choicementioning
confidence: 99%
“…We begin by reviewing language and paradigm trends in introductory programming courses. We consider paradigm along with language because languages may be taught in a manner that does not take advantage of the paradigm to which a language belongs [27,28]. We also look at trends in industry.…”
Section: Language Choicementioning
confidence: 99%
“…An Australasian census of introductory programming courses was conducted in (de Raadt, Watson and Toleman, 2002) and again in 2003. The most recent census uncovered 85 introductory programming courses (71 in Australia and 14 in New Zealand).…”
Section: Australasian Contextmentioning
confidence: 99%